Analisis Pengendalian Persediaan Bahan Baku Menggunakan metode Just In Time (JIT) pada CV. Rumah Mesin - Ramadani, Hani; Dwinugroho, Theofilus Bayu (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze raw material inventory management utilizing the Just In Time (JIT) method as an effort to improve operational efficiency at CV. Rumah Mesin. The main problems faced by the company include excess stock, late delivery, and high storage costs, which result in various types of waste. This investigation employs a qualitative descriptive approach with data collection through observation, interviews, documentation, and raw material procurement reports in 2024. Through inventory cost analysis using company policy calculations, the Economic Order Quantity (EOQ) method, and the Just In Time (JIT) method, it was revealed that JIT was able to provide significant cost savings. The total inventory cost according to company policy calculations reached Rp 14,859,487.68, - then it can be reduced to Rp 6,345,434.65, - after using the JIT method, resulting in a reduction of 57.34%. The JIT method also contributes to reducing waste in the form of overstock, waiting time, and storage accumulation. The investigation outcomes show that JIT is an effective method in increasing inventory control efficiency and supporting the smooth production process at CV. Rumah Mesin.